Case report: Thyroid carcinoma invading trachea: Multidisciplinary resection and reconstruction assisted by extracorporeal membrane oxygenation - He, Bo; Zhang, Shixin; Ren, Lin; Zhou, Yi; Chen, Qiao; Tang, Jinghua; Zhang, Yi; Tang, Meng; Qiu, Yang; Wang, Haidong (Frontiers in Oncology, 2023)
Background: When thyroid cancer invades the trachea, tumor resection and trachea reconstruction are required. Although the traditional way of anesthesia and tracheal intubation can maintain the necessary ventilation function during the operation, the tracheal intubation affects the surgical field of vision, and is not conducive to the protection of the recurrent laryngeal nerve beside the trachea during the operation. Case Presentation: Extracorporeal membrane oxygenation(ECMO) is used to replace traditional tracheal intubation in the process of resection and end-to-end anastomosis of tracheal tumors and complete tracheal tumor resection and trachea reconstruction are achieved. Conclusion: Using ECMO for thyroid carcinoma resection, invaded trachea resection and trachea reconstruction is safe and effective, which reduces the obstruction of endotracheal intubation on operative field, guarantees the rapid and efficient end to end anastomosis in the upper trachea, and clearly avoids laryngeal recurrent nerve injury in the process of anastomosis.